Investment Decisions under Uncertainty: Application of Estimation Risk in the Hillier Approach - Chen, Son-Nan; Moore, William T. (Journal of Financial and Quantitative Analysis, 1982)
Son-Nan Chen, William T. Moore, Investment Decisions under Uncertainty: Application of Estimation Risk in the Hillier Approach, The Journal of Financial and Quantitative Analysis, Vol. 17, No. 3 (Sep., 1982), pp. 425-440